Mechanism of liposome destabilization by polycationic amino acids. Issue 3 (June 1995) - Epand, Richard M.; Lim, Wendy
Abstract : Polycationic amino acids induce the leakage and fusion of liposomes containing anionic lipids. We have investigated the nature and extent of the changes in membrane physical properties caused by these polypeptides which could result in the observed membrane destabilization. We found that in the range of pH 5 to pH 7 both poly-l -histidine and poly-l -lysine were ineffective in shifting the bilayer to hexagonal phase transition temperature of dielaidoylphosphatidylethanolamine, either in the presence of absence of 1-palmitoyl-2-oleoylphosphatidylserine. We also studied the gel to liquid crystalline phase transition properties of 1:1 mixtures of phosphatidylserine and phosphatidylethanolamine, both in dimyristoyl forms as well as the 1-palmitoyl-2-oleoyl forms, as a function of pH and in the presence and absence of polycationic amino acids. We observed that these two lipids were largely miscible at all pH values and in the presence and absence of the polypeptides. However, there was some increased tendency for phase separation at higher pH and in the absence of polypeptide. Thus neither changes in curvature strain nor lateral phase separation induced by the polycationic amino acids could account for their marked ability to induce leakage and fusion. Phosphatidylethanolamine labelled with pyrene on one of the acyl chains gives rise to fluorescent emission from both monomer and excimer forms. The ratio of emission intensity from these two forms is indicative of lateral phase separation and the degree of lateral mobility of this probe. In equimolar mixtures of the 1-palmitoyl-2-oleoyl forms of phosphatidylserine and phosphatidylethanolamine in the liquid crystalline phase at 30 °C we find little effect of pH on the ratio of excimer to monomer emission intensity. However poly-l -lysine markedly lowers the fraction of excimer emission from these liposomes through the pH range from 5 to 7. Poly-l -histidine lowers the excimer to monomer emission ratio at pH 5 but not at pH 7. This is opposite to what one would expect for lateral phase separation and is interpreted at being the consequence of the polypeptide lowering the rate of lateral diffusion of the lipids. This effect of poly-l -histidine is observed over a range of temperatures from 0 to 40°C in both gel and liquid crystalline phases. There is no evidence from the behaviour of the pyrene fluorescent probe for lipid interdigitation. We conclude that the promotion of leakage and fusion in anionic liposomes by polycationic amino acids is not a result of large changes in the physical properties or arrangements of the lipids but rather to a surface binding of the polyamino acids.